REQUIREMENTS FOR APPLYING THE EFQM MODEL AT THE UNIVERSITY OF MISAN - Alaa Abdulsalam Mustafa (Scholar Express Journals, 2024)
The research aims to evaluate and know the administrative and organizational performance at the University of Misan using the European Foundation for Quality Management (EFQM) model, in order to determine high-quality services in accordance with modern developments, as well as knowing the requirements for implementing the EFQM system in the university under study. The research relied on the descriptive analytical method and a field survey in the faculties of the University of Misan, and the questionnaire was distributed to a sample that included 376 people. The data obtained were subjected to statistical analysis using SPSS V. 22. The research reached a number of conclusions, the most important of which is that most of the responses to all axes were moderate, and this indicates that the university under study is trying to implement the European model in the colleges affiliated with the University of Misan
Keywords: European Foundation; Quality Management; organizational performance